Variable Excitation Piezoelectric Energy Capture Device for Powering Scraper Conveyor Tension Detection Systems - Hezhe, Zhang; Cong, Wang (Manufacturing Technology Journal, 2024)
Past efforts which focused on the essential monitoring of the chain tension of scraper conveyers employed in fully mechanized coal mining operations have developed innovative power solutions based on the incorporation of piezoelectric devices that generate the electrical power required for the wireless transmission of chain tension data based solely on the vibrations of the scraper conveyor itself. However, these past studies have failed to evaluate the effects of different environmental factors on the electricity generating capacity of the piezoelectric devices. The present work addresses this issue by evaluating the maximum peak-to-peak voltage generated by a variable excitation piezoelectric device experimentally under a wide range of mechanical excitations, including static applied loads of 1600 g, 3200 g, and 4800 g with added oscillatory loads of different frequencies of 1.0 Hz, 2.0 Hz, and 3.0 Hz, and displacement amplitudes of 1.0 mm, 2.0 mm, and 3.0 mm. Compared with excitation frequency and excitation load the impact of an oscillatory load amplitude increasing from 1.0 mm to 3.0 mm on the obtained peak-to-peak voltages is quite profound, where the peak-to-peak voltage of the device increases by nearly 270%. The kind of piezoelectric power generation device which can adjust many kinds of external excitation is innovatively designed. The efficient and stable power supply of the piezoelectric device to the tension detection system of the scraper conveyor is realized.
Keywords: Variable excitation; Power generation characteristics; Scraper chain tension detection; PiezoelectricityANSYS simulation